Quantifying contact status and the air-breakdown model of charge-excitation triboelectric nanogenerators to maximize charge density - Yike Liu (Nature Portfolio, 2020)
Surface charge density is a key factor for developing high performance triboelectric nanogenerators. Herein, authors establish criteria to quantitatively evaluate the contact efficiency and air breakdown model on charge excitation triboelectric nanogenerators to maximize output charge density.